Clinical and Physiological studies of jaundice in the newborn infants and novel design and diagnostic method for neonatal hyperbilirubinemia determination - Hamidreza Shirzadfar (Archive of Biomedical Science and Engineering - Peertechz Publications, 2022)
Today, jaundice is one of the most common problems in newborns. Loss of Red Blood Cells (RBC) is the cause of jaundice. RBC rupture is known as hemolysis, and if hemolysis occurs faster than the liver excretes, bilirubin levels in the body rise and leading to jaundice. Bilirubin is directly soluble in water and is transported to the liver and excreted in stages, most of which is excreted in the feces and a small amount is excreted in the urine. Measuring bilirubin levels in infants is one of the essential tests after birth. In measuring the amount of jaundice in infants, complex components such as the formation of body organs, compounds on the skin of the infant, and other parameters are involved. Making a device to measure the amount of jaundice. The difference in the methods of measuring and treating jaundice in infants depends on the condition of the infant with jaundice. Non-invasive methods are used in infants with low bilirubin levels, but in acute and critical cases, invasive and direct methods are used. Jaundice tests are performed on both infected and healthy infants and are not limited to sick infants.